Optimized MPPT Controllers Using GA for Grid Connected Photovoltaic Systems, Comparative study. (July 2017) - Borni, A.; Abdelkrim, T.; Bouarroudj, N.; Bouchakour, A.; Zaghba, L.; Lakhdari, A.; Zarour, L.
Abstract: In this paper, comparisons between control strategies for grid connected photovoltaic system are proposed. MPPT algorithms P&O-PI, fuzzy logic-PI and optimized with genetic algorithm(GA) are used to control the DC/DC boost converter responsible to connect and extract the maximum power from the solar panel and transfer it to the DC-link. Another PI controller is used to maintain the DC-link voltage constant and close to its reference value under different conditions. Simulation results under different environmental and operating conditions are presented and discussed to verify the satisfactory of the performance of the proposed control strategies, in which the optimized fuzzy –PI controller by GA algorithms gives the better performance specification regarding the P&O-PI algorithm.